Application of hybrid Stage I palliation for patients with two ventricular cavities and hypoplastic left heart structures. (24th January 2018) - Higashida, Akihiko; Hoashi, Takaya; Kitano, Masataka; Shimada, Masatoshi; Nakata, Tomohiro; Ozawa, Hideto; Kurosaki, Kenichi; Ichikawa, Hajime
Abstract: OBJECTIVES: To assess the feasibility of hybrid Stage I palliation consisting of bilateral pulmonary artery bandings and ductal stenting for patients with 2 ventricular cavities and hypoplastic left heart structures. METHODS: Eleven consecutive patients who underwent hybrid Stage I palliation between 2010 and 2017 were enrolled. The diagnoses were interrupted aortic arch/coarctation of the aorta, ventricular septal defect and significant left ventricular (LV) outflow tract obstruction in 5 patients, critical aortic stenosis and reduced LV contraction in 3 patients and hypoplastic left heart complex in 3 patients. RESULTS: The median age at definitive surgery was 12 months (range 6–22 months). During the mean follow-up period of 24 months (range 9–83 months) following the definitive surgery, there was 1 death. Two patients with interrupted aortic arch/coarctation of the aorta did not undergo the Yasui operation but underwent arch repair and ventricular septal defect closure after the growth of the aortic valve and LV outflow tract. For 2 of the 3 patients with critical aortic stenosis, biventricular repair was performed. Of the 3 patients with hypoplastic left heart complex, 2 patients showed growth of the mitral valve and left ventricle following LV rehabilitation by balloon pulmonary artery dilatation or surgical debanding of the banded pulmonary arteries and subsequently underwent biventricular repair, which resulted in 1 death. CONCLUSIONS: Hybrid Stage I palliation would be a safe and beneficial treatment for patients with 2 ventricles, as a bridge to decide whether and how to achieve a biventricular repair and whether it should be preceded by a preliminary LV rehabilitation.